2004
DOI: 10.1177/0095244304039896
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-Chemical Reclamationof Waste Rubber Powder andIts Effect on the performanceof NR and SBR Vulcanizates

Abstract: Waste rubber powder (RP) was processed in a Brabenderpremixer under various conditions in the presence of reclaiming agents toconvert the RP into plastic mass (reclaimed rubber), then the obtained reclaimwas blended with both NR and SBR in different ratios. It was found that thebehavior of the reclaim in both NR and SBR is the same. The rheometriccharacteristics show that by increasing the reclaim ratio, the curing time wasdecreased and consequently the cure rate index was increased. Also themaximum torque of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 19 publications
2
29
1
2
Order By: Relevance
“…8) compared with original rubber vulcanizates, which reduces the maximum rheometric torque. The reason for decrease in scorch time is less evident, however, Phadke et al 18 and Yehia et al 17 observed a similar effect for filled natural rubber vulcanizate with ground scrap rubber. According to De et al, 1 the devulcanized rubber contains active cross-linking gel, which reduces the scorch time.…”
Section: Cure Characteristics Of the Vulcanizatesmentioning
confidence: 93%
See 1 more Smart Citation
“…8) compared with original rubber vulcanizates, which reduces the maximum rheometric torque. The reason for decrease in scorch time is less evident, however, Phadke et al 18 and Yehia et al 17 observed a similar effect for filled natural rubber vulcanizate with ground scrap rubber. According to De et al, 1 the devulcanized rubber contains active cross-linking gel, which reduces the scorch time.…”
Section: Cure Characteristics Of the Vulcanizatesmentioning
confidence: 93%
“…For revulcanized rubber, there is a decrease in maximum rheometric torque and scorch time. The revulcanized rubber vulcanizates contain less gel fraction 17 ( Fig. 8) compared with original rubber vulcanizates, which reduces the maximum rheometric torque.…”
Section: Cure Characteristics Of the Vulcanizatesmentioning
confidence: 99%
“…Due to the structure, GTR acts more like fillers which does not flow and agglomerates in the rubber matrix increasing the compound viscosity. The increase in viscosity translates to increase in the minimum torque [64]. RTR has more mobility compared to GTR, hence showing only slight increment in minimum torque [42].…”
Section: Cure Characteristicsmentioning
confidence: 99%
“…Many researchers observed reduction in scorch time with addition of GTR or RTR [42, 62-64, 66, 68-75]. This phenomenon is linked to presence of crosslink precursors and unreacted curatives in GTR/RTR or presence of active crosslinking sites in GTR/RTR which accelerate the crosslinking reaction upon heating [42,62,64,66,70,71]. Migration of crosslink precursors such as accelerator from GTR/RTR to the virgin rubber matrix leads to decrease in scorch time [42,69].…”
Section: Cure Characteristicsmentioning
confidence: 99%
“…However, all of these devulcanization methods are unable to produce a product that is similar to virgin rubber. Rubber recycling technologies such as mechanical [9,10], mechanochemical [11][12][13][14][15], ultrasonic [16], chemical [17][18][19], microwave [3,[20][21][22] and biological methods [23] have been developed with the targets of higher product quality and percent yield. Devulcanization provided the advantage of rendering the rubber suitable for reformulating and recycling into usable products [24].…”
Section: Introductionmentioning
confidence: 99%